Application of Ca-doped mesoporous silica to well-grouting cement for enhancement of self-healing capacity. (5th January 2016) - Lee, Seung-Woo; Jo, Minki; Kim, Ji-Whan; Kim, Taehee
Abstract: Carbonation has been considered as an alternative to prevent CO2 leakage. In this study, calcium-doped mesoporous silica (CDMS) was introduced into Portland cement as a promoter of carbonation. An admixture of CDMS and American Petroleum Institute (API) Class G Portland cement exposed to CO2 -saturated water was analyzed under geologic sequestration conditions (40 °C and 80 MPa) to assess the carbonation properties and self-healing effect of CDMS for CO2 storage. The capacity of CDMS to synthesize CaCO3 from CO2 via carbonation was identified in an in vitro crystallization test. Analysis of the cut surface of a cement core showed the rapid synthesis of CaCO3 including calcite and aragonite. Rietveld analysis was employed for quantitative phase analysis. The quantitative analysis of the cement carbonation showed that tricalcium silicate (C3 S) and dicalcium silicate (C2 S) play important roles in cement carbonation. Several crystal phases of CaCO3 were identified in this study including calcite, aragonite and amorphous CaCO3 . X-ray diffractometry (XRD), a field emission-scanning electron microscope (FE-SEM) equipped with an energy dispersive X-ray spectrometer (EDS), 29 Si MAS-NMR (magic angle spinning–nuclear magnetic resonance) spectrometry, thermogravimetry-differential thermal analysis (TG-DTA) and FT-IR (Fourier transform infrared spectroscopy) were applied to characterize the admixture. Graphical abstract: Highlight: Calcium doped mesoporous silica (CDMS) is synthesized along with Li et al. (2007) and applied to CO2 sealing cement. It was identified that CDMS can cause the rapid synthesis of CaCO3 . CDMS can enhance the healing capacity of wellbore cement against the mechanical damages such as cracks during CO2 storage.